Educational communities of inquiry theoretical framework, research, and practice - Akyol, Zehra; Garrison, D. Randy 1945- (Information Science Reference, 2013)
"This book is an extensive reference that offers theoretical foundations and developments associated with the CoI theoretical framework" - Provided by publisher
Includes bibliographical references
Keywords: Blended learning; Internet in education; E-Learning; Computerunterstützter Unterricht; Aufsatzsammlung